Enhanced P-Type GaN Conductivity by Mg Delta Doped AlGaN/GaN Superlattice Structure - Zhao, Ying (Materials (Basel), 2020)
A method of combining the AlGaN/GaN superlattices and Mg delta doping was proposed to achieve a high conductivity p-type GaN layer. The experimental results provided the evidence that the novel doping technique achieves superior p-conductivity. The Hall-effect measurement indicated that the hole concentration was increased by 2.06 times while the sheet resistivity was reduced by 48%. The fabricated green-yellow light-emitting diodes using the achieved high conductivity p-type GaN layer showed an 8- and 10-times enhancement of light output power and external quantum efficiency, respectively. The subsequent numerical calculation was conducted by using an Advanced Physical Model of Semiconductor Device to reveal the mechanism of enhanced device performance. This new doping technique offers an attractive solution to the p-type doping problems in wide-bandgap GaN or AlGaN materials.